(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2024)
The Digital Revolution has driven significant changes in the accounting field, especially in auditing, with the adoption of Artificial Intelligence (AI). This paper examines the impact of AI on auditing, highlighting how it has transformed traditional procedures. Through automation, AI has optimized processes such as transaction verification and fraud detection, allowing auditors to focus on more strategic analysis. A documentary methodology was used to analyze current applications of AI in auditing and its effects on accuracy and efficiency. The results show that AI improves the ability to detect anomalies and predict financial risks, bringing significant added value. However, it also poses ethical and regulatory challenges, which require an update of regulations and professional standards. In conclusion, AI is revolutionizing auditing, offering both opportunities and challenges that must be managed to maximize its potential.